Performance Analysis of Mobile Ad-Hoc Networks Based on TCP and UDP Traffic on AODV Protocol for Warship Communication - Alon Jala Tirta Segara; Afifah Dwi Ramadhani (Ikatan Ahli Informatika Indonesia Nusantara, 2023)
This research focuses on evaluating two key parameters in Mobile Ad-Hoc Networks (MANETs) that use the AODV protocol for warship communication, namely the packet delivery ratio (PDR) and end-to-end delay. PDR describes the percentage of data packets that successfully reach their destination without loss or damage during transmission. The study will analyze and compare PDR in MANETs with TCP and UDP traffic to understand the reliability and efficiency of the AODV protocol in data delivery. Furthermore, the research will also assess end-to-end delay, which measures the time it takes data packets to reach their final destination. Evaluating this delay will provide insights into the network's responsiveness in transmitting data between source and destination. The results of this research will offer valuable information about the performance of MANETs using the AODV protocol with TCP and UDP traffic. These findings can be used to optimize warship communication systems by selecting the most suitable protocol and traffic to achieve high PDR and minimal end-to-end delay; this study has the potential to serve as a critical foundation for developing reliable and efficient mobile ad hoc networks for military communication in dynamic and challenging environments.